An immunoregulation PLGA/Chitosan aligned nanofibers with polydopamine coupling basic fibroblast growth factor and ROS scavenging for peripheral nerve regeneration - Xiaokun Chen; Jihai Xu; Feng Qin; Ziyuan Yang; Xueyuan Li; Miao Yu; Ming Li; Yanhua Wang; Wang Xin (Materials Today Bio)
The repair and functional recovery of long-segment peripheral nerve injuries are crucial in clinical settings. Nerve conduits are seen as promising alternatives to autologous nerve grafts, but their effectiveness is limited by the controlled delivery of bioactive factors and meeting various functional requirements during different stages of repair. This research developed multifunctional nerve conduits using electrospinning and polydopamine (PDA) coating techniques to integrate bioactive substances. Chitosan-composite PLGA electrospun nerve conduits demonstrated exceptional mechanical properties and biocompatibility. Nanofibers with specific topological structures effectively promoted oriented cell growth. The PDA coating provided ROS scavenging and immune modulation functions. The bFGF growth factor attached to the PDA coating facilitated sustained release, enhancing Schwann cell functionality and stimulating neurite outgrowth. In a rat sciatic nerve defect model with a 10 mm gap, PLGA/CS-PDA-bFGF nerve conduits showed a positive impact on nerve regeneration and functional recovery. Consequently, nerve conduits with multiple functions modified with PDA-coated bioactive molecules are poised to be excellent materials for mending peripheral nerve injuries.